Impact of Human Resource Competence, IT Utilization, and Government Accounting Standards on Financial Statement Quality: The Moderating Role of Internal Control Systems - Nur Putri, Anggraeni (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
This study investigates the impact of human resource competence, information technology utilization, and government accounting standards on financial report quality, with the government's internal control system acting as a moderator. Using a sample of 71 respondents from the Research and Development Agency of the Ministry of Transportation, data was collected through a structured questionnaire and analyzed using multiple regression analysis. The findings reveal that information technology utilization positively influences financial report quality, while the government accounting standards show a negative impact, indicating potential issues in implementation. The study also finds that the government's internal control system needs to moderate the relationship between human resource competence and financial report quality and between information technology utilization and financial report quality. However, it moderates the relationship between government accounting standards and financial report quality positively. These results suggest the need for improved training, simplification of processes, and better change management to enhance the effectiveness of government accounting standards and the overall quality of financial reporting.